TJNPR 2020
DOI: 10.26538/tjnpr/v4i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Isosativan from Nigerian Red Propolis

Abstract: Propolis has been known for its medicinal use and as a source of diverse bioactive natural compounds. Phytochemical screening of propolis samples usually reveal the constituent compounds and the source of the sample. Chromatography is the simplest way of isolating natural compounds and thus the hexane and ethyl acetate extracts of propolis from Bonny in Rivers State, Nigeria were subjected to column chromatography and the isolated compounds were identified by LC-MS and NMR analysis. The compounds detected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The dried ethyl acetate extracts were subjected to column chromatography using ethyl acetate throughout over silica gel (230-400 mesh ASTM). 24…”
Section: Methodsmentioning
confidence: 99%
“…The dried ethyl acetate extracts were subjected to column chromatography using ethyl acetate throughout over silica gel (230-400 mesh ASTM). 24…”
Section: Methodsmentioning
confidence: 99%
“…Substitution of ring B to position C-3 instead of C2 produces the isoflavones (F5), isoflavanones (F6), and other moieties such as isoflavans (Structure F7) and pterocarpans (Structure F8). Many flavonoids have been identified in propolis; recent examples include isosativan, (2 -hydroxy-7,4 -dimethoxyisoflavan), liquiritigenin (45), isoliquiritigenin, formononetin (46), vestitol (21), neovestitol, medicarpin, 7-O-neovestitol, pinobanksin (47), pinocembrin, chrysin, and pinobanksin-3-O-acetate, astrapterocarpan, 3,8-dihydroxy-9-methoxy-pterocarpan, broussonin B, 8-prenylnaringenin (20), and gerontoxanthone H (12) [37][38][39].…”
Section: Flavonoidsmentioning
confidence: 99%
“…There is currently an intense search for alternative safe anti-Leishmania chemotherapy from propolis. Several studies have shown that propolis obtained from diverse origins possesses antileishmanial activity due to the presence of flavonoids [16][17][18][19][20][21][22][23][24] (37)) was found to possess much better antileishmanial activity than Ecuadorian propolis samples rich in triterpenic alcohols and acetyl triterpenes and inhibited the growth of L. amazonensis amastigotes and promastigotes [63]; structures are shown in Figure 6. One of the common factors usually evaluated when investigating the pharmacological activities of propolis is isolating the active component and testing it against a pathogen.…”
Section: Anti-leishmania Effects Of Propolismentioning
confidence: 99%